2014
DOI: 10.1590/0104-9224/si1903.06
|View full text |Cite
|
Sign up to set email alerts
|

Influencia de las mezclas de gases Ar-He y Ar-He-O2 en la soldabilidad de la aleación de aluminio AA5083-O usando Proceso GMAW-P automatizado

Abstract: Resumen La problemática en las empresas fabricantes de estructuras y construcciones soldadas en aluminio se centra en la disminución de las propiedades mecánicas de las uniones soldadas influenciada

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Controlling the appropriate ferrite-austenite ratio (1:1) is an excellent method to improve the strength and toughness of dual-phase stainless steel [31]. The crystal defects can reduce the strength of welded joints because it promotes dislocation movement and crack initiation in tensile process [32,33]. It follows from the above that the hardness of No.2 sample is higher than that of No.1 due to the disappearance of faults in microstructure, and the hardness of No.3 sample is almost unchanged, which benefits by adding 2%N 2 into pure Ar gas that can promote the ferrite-to-austenite transformation and obtain the appropriate ferrite-austenite ratio in WS and HAZ (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Controlling the appropriate ferrite-austenite ratio (1:1) is an excellent method to improve the strength and toughness of dual-phase stainless steel [31]. The crystal defects can reduce the strength of welded joints because it promotes dislocation movement and crack initiation in tensile process [32,33]. It follows from the above that the hardness of No.2 sample is higher than that of No.1 due to the disappearance of faults in microstructure, and the hardness of No.3 sample is almost unchanged, which benefits by adding 2%N 2 into pure Ar gas that can promote the ferrite-to-austenite transformation and obtain the appropriate ferrite-austenite ratio in WS and HAZ (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Weldability of aluminium alloys AA5083 using conventional fusion welding process has been widely studied [6], [7]. The results of those studies showed that, even though, values of Sut in AA5083-O welded joints using GMAW-P process present similar values to metal base, problems such as porosities and microcracks are still present [7]. Solid-state welding processes appear as an interesting alternative aiming to enhance weldability of this kind aluminium alloys [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as the oxidation potential of the gas increases, the strength and hardness of the weld decreases. This occurs because the oxygen components increase the number of oxide inclusions and reduce the level of magnesium and silicon in the material [10].…”
mentioning
confidence: 99%